Network Management in Software-Defined Network: A Survey. Issue 1 (February 2021) - Rasool, Zaid Ibrahim; Ali, Ridhab Sami Abd; Abdulzahra, Musaddak Maher
Abstract: SDNs are developed networks that focus on the separation of control aircraft and data. This new model is designed to simplify network management and enable research innovations. It explains the traditional system of SDNs and issues related to the traditional system. This paper explains the background of SDN technology and architecture. At the end of the research, SDN enhances scalability, flexibility, reliability, high availability, security and performance. This paper has tried to simplify and explain every problem with the SDN network and provided an overview of the SDN network general structure, the basics of network management in SDN, and the main challenges in SDN.